The discursive construction of the nation: Serbhood as the other in the construction of Montenegrin national identity - Mitrović Sava (Srpska Politička Misao)
Considering nations as socially constructed communities, the author examines the role of otherness in forming the national identity in the case study of contemporary Montenegrin identity. Drawing upon the thesis that distancing from Serbian national features played a key role in the construction of the Montenegrin nation, the author presents and explains processes of marginalisation and stigmatisation of Serbhood, understood as everything implicitly or explicitly related to Serbia as a country and/or Serbs as a people. After providing theoretical and methodological observations, the subsequent section offers a critical literature review on questions surrounding Montenegrin identity. In the central section of the paper, the discourse on Serbian otherness is deconstructed. Specifically, by employing the critical discourse analysis method, the author scrutinises how this discourse constructs identity and shapes social reality in Montenegro. This section comprises three subsections. The first thematically encompasses the discourse on the Podgorica Assembly of 1918 and related events in Montenegro; the second analyses the discourse on the Serbian Orthodox Church during the rule of the Democratic Party of Socialists, while the third presents a continuity of anti-Serb discourse after the fall of DPS. The research findings show that, alongside legal, foreign policy, linguistic, symbolic, and other distancing from Serbia and Serbhood, the construction of contemporary Montenegrin identity hinged on a discourse that not only suppressed Serbhood but also portrayed it as a hostile otherness and a threat to the mere existence of Montenegro.